Inorganic perovskite solar cell based on surface halide substitution and preparation method thereof
By spin-coating dimethylamine halide solution on the surface of the perovskite layer and annealing treatment, the halide substitution reaction on the surface of the perovskite layer is caused to form a gradient inorganic perovskite component, which solves the problem of poor stability of the CsPbI3 perovskite film and improves the photoelectric efficiency and stability of inorganic perovskite solar cells.
Patent Information
- Application Number
- CN202411785979.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The CsPbI3 perovskite film has poor stability at room temperature and is easily converted into an optically inactive delta phase, resulting in the limitation of the stability and photoelectric efficiency of inorganic perovskite solar cells.
By spin-coating dimethylamine halide (DMAX) solution on the perovskite layer surface and annealing treatment, the halide substitution reaction on the perovskite layer surface is caused to form a gradient inorganic perovskite component CsPbI3-yXy (X = Br or Cl), which induces equivalent compression strain to improve the phase stability and photoelectric efficiency of the film.
The phase stability and photoelectric efficiency of the CsPbI3 perovskite film have been improved, and the photoelectric conversion efficiency of solar cells has reached 21.2% or above, and there is almost no efficiency loss after long-term use.
Smart Images

Figure CN119816084A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solar cells, and in particular relates to an inorganic perovskite solar cell based on surface halide substitution and a preparation method thereof. Background Art
[0002] Perovskite solar cells have excellent optoelectronic properties, such as high carrier mobility, long carrier diffusion length and high defect tolerance, making them the most promising new type of solar cells. The laboratory-certified efficiency of organic-inorganic hybrid perovskites has reached 26.7%, which is close to the energy conversion efficiency of commercial silicon. However, due to the presence of volatile organic cations (such as methylamine and formamidine), organic-inorganic hybrid perovskites have poor chemical and thermal stability, which has led to more and more widespread attention to inorganic perovskite solar cells with higher stability in recent years.
[0003] Among many inorganic perovskite materials, CsPbI3 has an ideal band gap of 1.7eV, which makes it promising for application in single-junction and multi-junction solar cells. However, the black phase CsPbI3 with high optical activity has poor stability at room temperature and is easily transformed into the optically inactive δ phase. Therefore, how to stabilize the black phase CsPbI3 has become a technical problem that needs to be solved urgently.
[0004] Relevant studies have pointed out that residual tensile strain is the main factor causing phase instability of CsPbI3 perovskite films under inert atmosphere. Generally, the appearance of residual tensile strain can be attributed to the mismatch of thermal expansion coefficients between the perovskite film and the substrate during high-temperature annealing crystallization. The presence of residual tensile strain will further promote the formation of defects and lead to non-radiative recombination losses. At the same time, studies have found that perovskite films with residual compressive strain have better black phase stability than perovskite films with residual tensile strain or no residual strain. Therefore, inducing residual compressive strain in CsPbI3 perovskite films may be an effective solution to improve the stability of inorganic perovskite solar cells. Summary of the invention
[0005] The present invention provides an inorganic perovskite solar cell based on surface halide substitution and a preparation method thereof, constructs benign compressive strain of CsPbI3 perovskite, and improves the photoelectric efficiency of the solar cell and the phase stability of the film.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: An inorganic perovskite solar cell based on surface halide substitution, wherein the perovskite layer in the solar cell is a modified perovskite layer, a dimethylamine halide (DMAX, X = Cl or Br) solution is spin-coated on the surface of the perovskite layer and annealed, during the substitution process, DMAX only reacts with the surface of the perovskite layer and is subsequently removed by annealing, the reaction stops, the components of the perovskite layer except the surface do not change, the dimethylamine cations are easily removed during the film annealing crystallization process, and the purity of the inorganic film components can be ensured.
[0007] The solvent of the dimethylamine halide (DMAX, X = Cl or Br) solution is isopropyl alcohol (IPA), N,N-dimethylformamide (DMF) or dimethyl sulfoxide (DMSO); The concentration of the dimethylamine halide (DMAX, X = Cl or Br) solution is 0.5-2 mM; The dimethylamine halide (DMAX, X = Cl or Br) solution is spin-coated on the surface of the perovskite film at a rotation speed of 3000-6000 rmp; The annealing temperature is 100-300° C., and the annealing time is 1-10 minutes; The perovskite film is an inorganic perovskite film, and the structure of the inorganic perovskite is ABX3, wherein A is mainly Cs, B is one or more of Pb, Sn, and Ge, and X is one or more of I, Br, Cl, and F.
[0008] The core functional layer of the solar cell can be a formal structure and a trans structure. The formal structure includes an electron transport layer, a perovskite light absorption layer, and a hole transport layer from the substrate upward; the trans structure includes a hole transport layer, a perovskite light absorption layer, and an electron transport layer from the substrate upward.
[0009] Beneficial effects: The present invention provides an inorganic perovskite solar cell based on surface halide substitution and a preparation method thereof, which has the following advantages over the prior art: 1. Treat CsPbI3 film with DMAX (X = Cl or Br) and anneal it. Annealing can drive the crystallization of CsPbI3 film and evaporate DMA at the same time. + To ensure the purity of CsPbI3 film components, DMAX only reacts with the film surface, turning its surface components into mixed halide CsPbI 3-y X y (X = Br or Cl), when I - By the smaller Br - or Cl - When substituted, a gradient of inorganic perovskite components CsPbI is formed on the perovskite surface 3-y X y(X = Br or Cl), which reduces the lattice size. This surface halide substitution causes lattice contraction, thereby inducing an equivalent compressive strain near the perovskite surface. The uniformly distributed compressive strain along the film effectively passivates the surface halide vacancies, helps stabilize the phase state of the CsPbI3 perovskite film and suppresses the light-induced ion migration. 2. The halide components on the surface of perovskite are replaced, providing additional halogen anions to passivate the halogen vacancies on the surface, making the CsPbI3 film have fewer defects and effectively suppressing non-radiative recombination, which helps to improve the photoelectric efficiency of solar cells; 3. The modified solar cell of the present invention has a 2 Small size and 23.9 cm 2 The solar cell modules achieved a power conversion efficiency (PCE) of 21.2% and 19.2%, respectively, with almost no loss in PCE after these cells were exposed to air for more than 1,000 hours and operated continuously under maximum power point tracking and 1 sun for more than 3,200 hours; 4. The surface halide substitution used in the present invention is mainly to use DMAX (X = Cl or Br) to treat the CsPbI3 film and then anneal it. The method is simple, easy to operate and economical. The solar cell device treated not only has a significantly improved photoelectric efficiency, but also has significantly improved stability. The present invention has both important scientific significance and extremely high industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 Schematic diagram of halide substitution at the surface of CsPbI3 perovskite after treatment with DMAX (X = Br or Cl) in an embodiment of the present invention; Figure 2 is a graph showing the relationship between the peak position of the (110) plane of CsPbI3 extracted from the grazing incidence X-ray diffraction pattern and different X-ray incident angles in an embodiment of the present invention; Figure 3 The current-voltage (JV) curves of Comparative Example 1 and Examples 1, 2, and 3; Figure 4 The efficiency champion device in Example 4 (effective area 23.9 cm 2 , the current-voltage (JV) curve and power curve with a geometric filling factor of about 0.93; Figure 5 The graph is a functional relationship between the normalized photoelectric efficiency and the aging time of the packaged devices prepared in Comparative Example 1 and Examples 1, 2, and 3 at maximum power output in air at 40°C and under constant 1 sun illumination. DETAILED DESCRIPTION
[0011] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments: Example 1
[0012] A method for preparing an inorganic perovskite solar cell based on surface halide substitution comprises the following steps: The pre-patterned FTO substrate was washed with deionized water, acetone and isopropanol for 15 minutes each, dried with nitrogen and then treated with UV-ozone for 30 minutes. For the electron transport layer, a 2-propanol solution (7 mL) containing 0.6 mL of di(acetylacetonato)titanate diisopropyl solution and 0.4 mL of acetylacetone was spray pyrolyzed at 450°C using oxygen as the carrier gas to deposit a dense titanium dioxide layer of about 40 nm, which was then treated with UV-ozone for 15 minutes. The titanium dioxide dense film was immersed in a 5 mM isopropanol solution of butyltrimethoxysilane for 3 hours to modify the strain release layer and suppress the lattice distortion of the buried interface of the film. After that, the substrate was rinsed in isopropanol and then dried under a nitrogen flow. For the CsPbI3 active layer, a 0.6 M CsI, PbI2, and DMAI solution was prepared by dissolving stoichiometric CsI, PbI2, and DMAI in N,N-dimethylformamide in a molar ratio of 1:1:1.3. The CsPbI3 precursor solution was cast on the substrate and then spun at 2800 rpm for 30 s. The film was then thermally annealed at 215 °C for 4.5 min. For surface halide substitution treatment, DMAI was dissolved in isopropanol at a concentration of 15 mM and spin-coated at 5000 rpm for 30 s. Then, the film stack was annealed at 210 °C for 1 min. All annealing processes were performed in a drying oven with humidity controlled at 23-25%. Subsequently, a hole transport layer was deposited on top of the active layer by spin-coating a PTAA solution at 3000 rpm for 30 s. The PTAA solution was prepared by mixing PTAA (12 mg ml -1 ) was dissolved in toluene and 6 μL Li-TFSI (340 mg ml -1 acetonitrile solution) and 6 μL 4-tert-butylpyridine; finally, the solar cell was completed by evaporating a 100 nm thick gold top electrode. 2 ) mask, and 100 nm and 200 nm magnesium fluoride layers were evaporated on the glass surface of the FTO substrate and the gold surface of the device as anti-reflection layer and initial protection layer, respectively. Example 2
[0013] Basically the same as Example 1, the specific difference is that for the surface halide substitution treatment, DMABr was dissolved in isopropanol at a concentration of 15 mM and spin-coated at 5000 rpm for 30 s, and then the film stack was annealed at 210 °C for 1 minute. Example 3
[0014] Basically the same as Example 1, the specific difference is that for the surface halide substitution treatment, DMACl was dissolved in isopropanol at a concentration of 15 mM and spin-coated at 5000 rpm for 30 s, and then the film stack was annealed at 210 °C for 1 minute.
[0015] Comparative Example 1 It is basically the same as Example 1, with the specific difference that: no surface halide substitution treatment is performed, that is, DMAX (X = Cl or Br) is not used to treat the CsPbI3 film.
[0016] Figure 1 Schematic diagram of halide substitution at the CsPbI3 perovskite surface after treatment with DMAX (X = Br or Cl) salts, as shown in Figure 1 As shown, when the CsPbI3 perovskite surface is modified with DMAX (X = Br or Cl) salt, Br - and Cl - Substituting I on the surface of CsPbI3 film - , forming a gradient of inorganic perovskite components CsPbI on the perovskite surface 3-y X y (X = Br or Cl), which reduces the lattice size and generates residual compressive strain along the film.
[0017] Figure 2 This is a graph showing the relationship between the peak position of the (110) plane of CsPbI3 extracted from the grazing incidence X-ray diffraction pattern and the change with different X-ray incident angles. It is more clear to see the halide substitution occurring on the film surface.
[0018] Figure 3 The JV curve diagram of comparative example 1 and embodiments 1, 2, and 3 shows that the open circuit voltages of comparative example 1 and embodiments 1, 2, and 3 have an obvious upward trend, so the photoelectric efficiencies of embodiments 1, 2, and 3 are all increased compared with comparative example 1, among which the photoelectric efficiency of embodiment 3 is the highest, reaching 21.2%. Example
[0019] The modules connected in series were obtained by interconnecting P1, P2 and P3 by laser structuring using a laser scribing system equipped with a 1064 nm laser with a maximum power of 20 W. The P1 line was laser scribed on the FTO substrate using a power of 10 W, a pulse width of 100 ns and a repetition rate of 100 kHz to obtain a scribe width of 50 μm. The substrate was cleaned with detergent, acetone and isopropanol in sequence, each step for 15 minutes, and dried by nitrogen. The FTO was then treated with UV-ozone for 30 minutes. The titanium dioxide layer and the strain release layer were deposited on the single cell using the same method as in Example 1. The CsPbI3 precursor solution was scraped onto the ITO glass substrate covered with the titanium dioxide layer and the strain release layer at a moving speed of 30 mm / s and a gap of 200 μm. A nitrogen knife operated at 25 psi was used during scraper coating; the wet film was then annealed at 215 °C for 4.5 minutes. For surface halide substitution treatment, the nitrogen knife was heated to 200 psi. The DMACl solution was blade coated at a speed of 100 mm / s with a gap of 150 μm, and then the stack was thermally annealed at 210 °C for 1 min and the PTAA solution was blade coated at a speed of 15 mm / s with a gap of 200 μm. For the deposited layers, the P2 line was laser scribed at a power of 6 W, a pulse width of 100 ns, and a repetition rate of 70 kHz to obtain a scribe width of 150 μm. Then gold (100 nm) was deposited as an electrode. The P3 line was laser scribed on the electrode using a power of 6 W, a pulse width of 100 ns, and a repetition rate of 70 kHz to obtain a scribe width of 100 μm. 100 and 200 nm magnesium fluoride layers were evaporated on the glass side of the FTO substrate and the gold side of the device as antireflection layer and initial protection layer, respectively. The geometric fill factor was about 0.93.
[0020] Figure 4 The efficiency champion device in Example 4 (effective area 23.9 cm 2 From the JV curve and power curve diagram with a geometric fill factor of about 0.93, it can be seen that the photoelectric efficiency of the large-area champion device is as high as 19.2%, indicating that the technology of the present invention can be effectively applied to large-area modules.
[0021] Figure 5 Figure 2 is a graph showing the normalized photoelectric efficiency of the encapsulated devices prepared in Comparative Example 1 and Examples 1, 2, and 3 as a function of aging time at maximum power output in air at 40°C under constant 1 sun illumination. The initial efficiency of Comparative Example 1 decreased by more than 20% after 1000 h. In contrast, the efficiency of Example 1 showed significantly enhanced operational stability due to the surface passivation effect, T 80The life span is 2400 h. In sharp contrast, the efficiency of Example 2 still maintains more than 90% of its initial efficiency after 3200 h of operation, while the efficiency of Example 3 has a negligible loss in its initial efficiency (less than 1%) after 3200 h of continuous operation.
[0022] The above description is only a preferred embodiment of the present invention. It should be pointed out that those skilled in the art can make corresponding changes and adjustments to the technical approach of the present invention without departing from the basic principles of the present invention. These changes and adjustments all fall within the protection scope of the present invention.
Claims
1. An inorganic perovskite solar cell based on surface halide substitution, characterized in that: The halogen elements of the surface components of the perovskite layer in the solar cell are replaced.
2. The inorganic perovskite solar cell based on surface halide substitution according to claim 1, characterized in that: The surface component of the perovskite layer is CsPbI 3-y X y , where y = 1~3, X = Cl or Br.
3. A method for preparing an inorganic perovskite solar cell based on surface halide substitution, characterized in that: A dimethylamine halide solution is spin-coated on the surface of the perovskite layer and then annealed.
4. The method for preparing an inorganic perovskite solar cell based on surface halide substitution according to claim 3, characterized in that: The concentration of the dimethylamine halide solution is 0.5-2 mM.
5. The method for preparing an inorganic perovskite solar cell based on surface halide substitution according to claim 3 or 4, characterized in that: The solvent of the dimethylamine halide solution is isopropanol, N,N-dimethylformamide or dimethyl sulfoxide.
6. The method for preparing an inorganic perovskite solar cell based on surface halide substitution according to claim 3 or 4, characterized in that: The rotation speed of spin coating the dimethylamine halide solution on the surface of the perovskite film is 3000-6000 rmp.
7. The method for preparing an inorganic perovskite solar cell based on surface halide substitution according to claim 3, characterized in that: The annealing temperature is 100-300° C., and the annealing time is 1-10 minutes.
8. The method for preparing an inorganic perovskite solar cell based on surface halide substitution according to claim 3, characterized in that: The perovskite film is an inorganic perovskite film with an ABX3 structure, wherein A is Cs, B is one or more of Pb, Sn, and Ge, and X is one or more of I, Br, Cl, and F.
9. The method for preparing an inorganic perovskite solar cell based on surface halide substitution according to claim 3, characterized in that: The solar cell core functional layer is a regular structure or a trans structure.
10. The method for preparing an inorganic perovskite solar cell based on surface halide substitution according to claim 9, characterized in that: The formal structure comprises an electron transport layer, a perovskite light absorbing layer, and a hole transport layer from the substrate upward; the trans structure comprises a hole transport layer, a perovskite light absorbing layer, and an electron transport layer from the substrate upward.
Citation Information
Patent Citations
Surface defect passivated metal halide perovskite nanocrystal, and preparation method and application thereof
CN110205118A
Preparation method of Cs<n>FA<1-n>PbX<3> perovskite thin film
CN111129319A
Method for regulating and controlling stress of perovskite thin film by using chemical cross-linking agent and perovskite solar cell
CN113285031A
Method capable of preparing FAxCs1-xPbX3 high-quality perovskite thin film in large area
CN116528637A
Method for preparing CsPbBr3 solar cell with high open-circuit voltage through inorganic passivation
CN116864570A